TPACK-Integrated Learning Media Assisted by Appypie to Improve the Literacy Skills of Elementary School Teacher Education (ESTE) Students - Ari Suriani; Elfia Sukma; Chandra Chandra; Lili Dasa Putri (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
TPACK is a 21st-century competency that must be mastered by lecturers, including prospective lecturers. Much research has been conducted on TPACK, but research linking TPACK with learning media is still limited. Therefore, researchers need to conduct research that connects integrated learning media with TPACK using Android with the Appypie system to increase digital literacy. This research aims to produce TPACK-integrated learning media assisted by APPYPIE that is valid, practical and effective for PGSD FIP UNP students. This type of research is research and development. The development model used in this research is the 4-D model. This model consists of four stages, namely, definition, design, development and dissemination. The research results show that literacy skills play an important role in determining student learning success. TPACK-integrated learning media assisted by APPYPIE has been proven to increase student interest in lectures. This makes students interested in the lecture material so that it can increase students' understanding of the course.